Edible marijuana and cycle ergometer exercise - Ewell, Taylor Russell; Bomar, Matthew Charles; Abbotts, Kieran Shay Struebin; Butterklee, Hannah Michelle; Dooley, Gregory P.; Bell, Christopher (Frontiers in Physiology, 2022)
Purpose: There is extensive public and scientific interest in the influence of cannabis and the psychoactive cannabinoid, delta-9-tetrahydrocannabinol (THC), on exercise performance. Unfortunately, recent, up-to-date studies are lacking. The aim of the current study was to address the hypothesis that ingestion of edible marijuana, prior to exercise, would have unfavorable effects on the physiological response to exercise and on exercise performance. Methods: 17 Healthy adult male and female habitual exercisers, who were regular users of cannabis products, were screened for study participation. 10 were enrolled, and data from 9 (8 males, 1 female, aged 25±3 years, with peak oxygen uptake of 56.5±11.7 ml/kg/min (mean ± SD)) were retained. Participation included two exercise sessions, each preceded by self-administration and ingestion of either edible marijuana (containing 10 mg THC) or placebo. Cardio-respiratory responses (via indirect calorimetry) to stationary cycle ergometer exercise (8 minutes at 50, 100 and 150 Watts) were recorded before completion of a 20-minute Functional Threshold Power test (FTP20) and a sprint test involving maximal effort until volitional fatigue. Results: Edible marijuana increased the concentration of circulating THC and THC metabolites, and evoked sensations of intoxication and altered psychoactive state. Cardio-respiratory responses to staged cycle ergometer exercise were normal and were unaffected by edible marijuana. Compared with placebo, edible marijuana did not influence FTP20 (Placebo 253±75 vs. THC: 251±72 W (mean±SD); P>0.45) or peak power output during the sprint test (Placebo: 710±201 vs. THC: 732±136 W; P=0.864). Conclusion: 10 mg of THC, when ingested prior to exercise by regular exercisers and habitual users of cannabis, had little effect on the physiological response to standardized cycle ergometer exercise, and was neither ergogenic nor ergolytic.